Evaluation of Educational School Environment and Academic Self-Evaluation of Adolescent Athletes and Non-Athletes - Ilona Tilindienė; Saulius Šukys; Saulius Kavaliauskas (Lithuanian Sports University, 2018)
Background. Grigaliūnienė, Vėlavičienė, Šulga, and Keblys (2007) have revealed that meaningful relationships with teachers are influenced by positive attitudes towards them with a good emotional atmosphere in the classroom and a positive microclimate between pupils and teachers. Many scientists point out that education in sports activities positively impacts the development of adolescents' communication and collaboration with peers and adults, adequate self-evaluation and other positive personality characteristics (Kremer-Sadlik & Kim, 2007; Ream & Rumberger, 2008). Research aim was to determine the evaluation of educational school environment and academic self-evaluation of 11-15-year-old adolescent athletes and non-athletes. Methods. The research was conducted in 2015. We questioned 209 adolescents, aged 11-15 years. In order to determine adolescents' attitudes towards school educational environment, the survey included the following scales: "Teachers'  help  for  pupils";  "Support  of  classmates";  "Positive  relationship  between  adolescents  and  school"; "Attitude towards socioeducational school environment"; "Loneliness at school", and "Academic self-evaluation". Results. The survey revealed that boys' attitudes to socioeducational school environment resulted to be better than  that  of  girls  (p  <  .05)  and  that  younger  adolescents  felt  more  help  from  the  teachers  at  school  than  older adolescents (p < .05), but they also pointed out that they experienced a stronger sense of loneliness at school (p < .05). More positive relationship was revealed between adolescent athletes and school (p < .05), but adolescent non- athletes had a better attitude to socioeducational school environment. Conclusion. It was found that although adolescent non-athletes had a better approach to socioeducational school environment, their peer reported having a better link with school. Keywords:  attitude, adolescent athletes, adolescent non-athletes, feeling at school, sports activity.